PKM Pelatihan Pembuatan Media Pembelajaran Berbasis AI Untuk Guru-Guru SMP Di Makassar - Lu'mu, Lu'mu; Ruslan, Ruslan; Hasanah, Hasanah; Muchtar, Akhyar; Burhan, Muh. Iswal (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) aims to enhance the capacity of teachers in Makassar in utilizing Artificial Intelligence (AI) technology as an innovative and adaptive learning medium in response to the demands of the digital era. The training was held on May 10, 2025, at the 'Aisyiyah Multipurpose Hall in South Sulawesi and was attended by 15 teachers from various educational levels. The training methods included material presentations, demonstrations of AI-based tools, and hands-on practice in creating learning media using AI platforms. The results of the activity showed that participants demonstrated high enthusiasm and were able to produce more engaging and interactive learning materials. This training is expected to serve as an initial step in the broader implementation of AI in education, and to make a meaningful contribution to improving the quality of teaching and learning processes in schools.